Monckeberg's arteriosclerosis: a case report of chronic endometritis presenting as postmenopausal bleeding. Issue 2 (February 2022) - Mercer, Victoria J.; Naseemuddin, Ather; Webb, Amanda
Abstract: Objective: Chronic endometritis is rarely reported in the postmenopausal population. Here, we describe a case of chronic endometritis in a patient who had undergone premature menopause that was later found to have Monckeberg arteriosclerosis (MocA) of the uterine vessels. Methods: A review of the literature revealed a single report of MocA affecting the uterine vessels and no reports in a patient who had undergone premature menopause. A case of a 69-year-old presenting with postmenopausal bleeding and having the diagnosis of chronic endometritis is described. Results: Following definitive management with hysterectomy, final histopathology showed MocA of the uterine vessels. Conclusions: The lack of reviews of chronic endometritis in postmenopausal women reveals a gap in the literature. Further studies are necessary to review MocA and decreased uterine perfusion in the context of a possible predisposition to chronic endometrial infection and/or inflammation.